Comparison of backward flow values in the sharp focus of light fields with polarization and phase singularity - Victor Kotlyar (Компьютерная оптика, 2019)
Using Jones matrices and vectors, we show that an optical metasurface composed of a set of subwavelength binary diffraction gratings and characterized by an anisotropic transmittance described by a polarization rotation matrix by the angle mφ, where φ is the polar angle, forms an m-th order azimuthally or radially polarized beam when illuminated by linearly polarized light, generating an optical vortex with the topological charge m upon illumination by circularly polarized light. Such a polarization-phase converter (PPC) performs a spin-orbit transformation, similar to that performed by liquid-crystal q-plates. Using a FDTD method, it is numerically shown that when illuminating the PPC by a uniformly (linearly or circularly) polarized field with topological charge m = 2 and then focusing the output beam with a binary zone plate, a reverse on-axis light flow is formed, being comparable in magnitude with the direct optical flow. Moreover, the reverse flows obtained when focusing the circularly polarized optical vortex with the topological charge m = 2 and the second-order polarization vortex are shown to be the same in magnitude.